»Ein Roman ist ein romantisches Buch« - Folkmann, Mads Nygaard (K&K - Kultur og Klasse, 2007)
Umulige fiktioner i den romantiske roman »Ein Roman ist ein romantisches Buch«. Impossible Fictions in the Romantic Novel In the Romantic period, the novel is regarded as a literary form that, by poetological necessity, makes experiments by means of literary representation possible. Seen in an European perspective this is almost solely a matter of early German Romanticism, Frühromantik, where Friedrich Schlegel and Novalis by formulating the novel as a specific, modern genre, try to state a new, revolutionary aesthetics. The article thus points at three characteristic features of the novel’s poetics within this context: 1) the novel contains a double poetics of formal heterogeneity and spiritual homogeneity; 2) the novel gets its value through its inherent epistemology of world views; 3) the novel of early German Romanticism understands itself in a productive split of an utopian vision that never can be fulfilled and an auto-reflexivity exactly because of the knowledge of permanent unfulfillment. Further,the article argues, an aesthetics of impossible fictions evolves as the potential and heritage of this kind of poetics. In the last part of the article, a novel of the Swedish (post-)Romantic author Carl Jonas Love Almqvist (1793-1866), Drottningens juvelsmycke (The Queen’s Tiara, 1834), is read as way of representing, through the constitution of the main character, Tintomara, a principle of the absolute that displays the borders of novelistic representation.